PENGEMBANGAN MODEL PEMBELAJARAN MEANINGFUL TEACHING ISSUES BASED ON SOCIAL CAPITAL (MUTIS MODEL) UNTUK MENINGKATKAN KETERAMPILAN INTERPERSONAL PESERTA DIDIK DALAM PEMBELAJARAN IPS - Mutiani, - (2023)
Mutiani (2002483). Development of a Meaningful Teaching Issues Based on Social Capital Learning Model (Mutis Model) to Improve Students' Interpersonal Skills in Social Studies Learning. Under the guidance of Prof. Dr. H. Disman, M.S., Prof. Dr. Drs. Ersis Warmansyah Abbas, BA., M.Pd., Dr. Erlina Wiyanarti, M.Pd. Based on the process and results achieved by social studies, learning requires interpersonal skills. Conceptually, interpersonal skills are interpreted as skills in communicating and collaborating. This is important, considering that skills are one of the conceptual frameworks for 21st-century skills. Improving interpersonal skills can be done by making an innovative constructive learning model to increase the active role of students. The research aims to describe the development of an effective learning model, Meaningful Teaching Issues based on Social Capital (Mutis Model), to improve students' interpersonal skills in social studies learning. This study uses a development approach to produce a learning model. The method used in this study is the Borg and Gall Research and Development (RnD) model. Ten research steps traverse the method. Observation, interviews, Focus Group Discussion (FGD), and questionnaires were used to collect data. The research was conducted in Banjarmasin and Banjarbaru, involving eight schools divided into two test activities (limited test and wide test). The sample was determined using a purposive technique in class VIII social studies at junior high school. The findings of the study are: (1) The social capital of the Banjar people has similar characteristics to social capital in other countries, which boils down to three things: trust, network, and norms; (2) The three social capitals of the Banjar community are then integrated as part of the learning model syntax; (3) |Meaningful Teaching Issues learning model based on Social Capital (Mutis Model), systematically arranged with six steps, namely: Problem Orientation and Identification, Trusting Students, Developing Network, Analyzing and Evaluating Problems, Norm Clarification, and Delivering Results; and (4) Development of the Mutis model based on expert testing, limited testing, and broad testing. Implementation of the Mutis model effectively improves students' interpersonal skills. This happens because the Mutis model contains trust between students to open up to each other to convey different information. The research concludes that applying the Mutis model can develop students' communication competence and improve the quality of interactions between teachers-students and students-students. The limitations of this study focus on the affective aspects of students. The existence of further research with a different focus is expected to strengthen the existence of the Mutis model. Keywords: Social Capital, Banjar Community, IPS Learning Model, Interpersonal Skills.